Kebijakan Kontroversial Dana Bos Tahun 2021 - Alghozi, Alan Alifudin; Setiawan, Farid; Mardiah, Ainun; Majmudin, Ahmad; Fitriani, Resti; Fadillah, Ayu Nur; Jannah, Miftahul (TSAQOFAH, 2022)
This research is a study that focuses on the analysis of educational policies recently issued by the Government of Indonesia, the Ministry of Education and Technology, namely Permendikbud No. 6 of 2021. This study aims to provide analysis and solutions to the policy of Permendikbud No. 6 of 2021 which stated that the disbursement of BOS Funds is discountinued to schools with less than 60 students for 3 consecutive years. This research was conducted through the study of literature (library research) such as books and websites. The method used for data analysis is descriptive qualitative analysis technique that can describe the main discussion and bring up the final solution. Based on the results of this study, the policy of the Minister of Education and Culture Number 6 of 2021 deserves to be revoked and reviewed.